Teknik Pencarian Hadith dalam Kajian: Analisis Hadith dalam Buku-Buku Motivasi di Malaysia - Asmori, Muhammad Faiz Fathi; Nazri, Mohd Arif; Hussin, Haziyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Statement of the hadith would not be complete if the source is not specified in the original reference books and expressed his status either accepted or rejected. Therefore, this article will introduce hadith search techniques (Takhrij Hadith) used in the study of hadith analysis. Seven guidelines been introduced in this article; First, present the material traditions (matan) from motivation books either by words or meaning or both. Second, doing takhrij hadith to trace the placed located hadith. Third, analyzing rijal hadith and bring forward Shajarah al-Asanid. Fourth, analyzing material traditions of hadith (matan). Fifth, provide the status of the hadith either accepted or rejected. Sixth, present the conclusions of the hadith. And lastly, identify shawahid and mutaba'ah as alternative for hadith that has been rejected if necessary.